Craniofacial phenotypes associated with Robinow syndrome. Issue 12 (25th November 2020) - Conlon, Christopher J.; Abu‐Ghname, Amjed; Raghuram, Anjali C.; Davis, Matthew J.; Guillen, Diana E.; Sutton, V. Reid; Carvalho, Claudia M. B.; Maricevich, Renata S.
Abstract: Robinow syndrome is characterized by mesomelic limb shortening, hemivertebrae, and genital hypoplasia. Due to low prevalence and considerable phenotypic variability, it has been challenging to definitively characterize features of Robinow syndrome. While craniofacial abnormalities associated with Robinow syndrome have been broadly described, there is a lack of detailed descriptions of genotype‐specific phenotypic craniofacial features. Patients with Robinow syndrome were invited for a multidisciplinary evaluation conducted by specialist physicians at our institution. A focused assessment of the craniofacial manifestations was performed by a single expert examiner using clinical examination and standard photographic images. A total of 13 patients with clinical and molecular diagnoses consistent with either dominant Robinow syndrome (DRS) or recessive Robinow syndrome (RRS) were evaluated. On craniofacial examination, gingival hyperplasia was nearly ubiquitous in all patients. Orbital hypertelorism, a short nose with anteverted and flared nares, a triangular mouth with a long philtrum, cleft palate, macrocephaly, and frontal bossing were not observed in all individuals but affected individuals with both DRS and RRS. Other anomalies were more selective in their distribution in this patient cohort. We present a comprehensive analysis of the craniofacial findings in patients with Robinow Syndrome, describing associated morphological features and correlating phenotypic manifestations to underlying genotype in a manner relevant for early recognition and focused evaluation of these patients.